Applied biomechanics for evidence-based training of Australian elite seated throwers - Frossard, L. A.; O'Riordan, A.; Goodman, S. (International Council of Sport Science and Physical Education Perspectives series, 2005)
Research in biomechanics is one method available to improve the understanding of the performance of elite seated throwers, which depends on the interaction between the design of the athletes` throwing frame and their throwing technique. The main purpose of this paper is to provide an outlook on the two approaches currently underlying this research. The specific objectives are (A) to describe the procedure, outcomes and limitations of the conventional approach, based on fundamental research, (B) to present the innovations and dynamic research procedure of an integrated approach based on applied research, as implemented by a multi-disciplinary team working together since 2000, from Athletics Australia (AA), the Australian Institute of Sport (AIS) and Queensland University of Technology (QUT). This approach relies on the integration of biomechanics within an evidence-based training framework. Furthermore, an example of the work conducted during training, in experimental conditions and during real-event around the foot placement of F33/34 throwers will be provided.